2015
DOI: 10.1038/nrneph.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C and its impact on renal transplantation

Abstract: Infection with hepatitis C virus (HCV) is the major cause of chronic liver disease that occurs after renal transplantation. Such infection is often acquired during dialysis while patients wait to undergo renal transplantation. Renal transplantation is considered the best treatment option for patients with HCV infection and end-stage renal disease, although acceptance of a kidney graft by the host immune system and patient survival are lower compared to patients who test negative for HCV. The approval of interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 115 publications
3
92
0
1
Order By: Relevance
“…35 Another study on monotherapy of interferon by Esforzado et al showed acure rate of 30-45% in ESRD patients. 36 As therapy of Peg IFN and RBV may cause post transplanted graft rejection, the safety of conventional BEMS Reports, Vol 2, Issue 1, Jan-Jun, 2016 treatment remains an issue to address 37,38 The rapid evolution of interferon-free regimen DAAs changed the perception about the treatment of chronic HCV in difficult to treat group. Difficult to treat group included HCV patients with severe Renal impairment including ESRD or kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…35 Another study on monotherapy of interferon by Esforzado et al showed acure rate of 30-45% in ESRD patients. 36 As therapy of Peg IFN and RBV may cause post transplanted graft rejection, the safety of conventional BEMS Reports, Vol 2, Issue 1, Jan-Jun, 2016 treatment remains an issue to address 37,38 The rapid evolution of interferon-free regimen DAAs changed the perception about the treatment of chronic HCV in difficult to treat group. Difficult to treat group included HCV patients with severe Renal impairment including ESRD or kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…76,84 HCV Treatment in the KT Recipient For the last two decades, the treatment of HCV infection in the post-transplant setting has not been an option in large part because of the unacceptable risk of rejection associated with the use of IFNbased regimens. [84][85][86][87] Furthermore, the IFNs are poorly tolerated, and SVR rates are only in the 45%-50% range. 88 As a consequence of this poor efficacy and high adverse event profile, treatment of HCV infection in the KT candidate and recipient has often been deferred.…”
Section: Grazoprevir and Elbasvirmentioning
confidence: 99%
“…6 The lower survival was related to the posttransplant progression of liver disease induced by the use of immunosuppressive regimens 7,8 and increased risk for development of extrahepatic complications of HCV infection, including posttransplant de novo or recurrent glomerular disease and new-onset diabetes mellitus. 9,10 However, despite these risks, renal transplant is still recommended in HCV-positive patients, as survival is significantly better in those who undergo transplant versus infected patients who remain on hemodialysis. 11,12 Immunosuppressive drugs and hepatitis C virus infection The natural course of HCV infection in kidney transplant patients is more complex than in nontransplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 Hepatitis C virus-related liver disease after kidney transplant The risk of developing posttransplant liver disease depends on the severity of the liver disease before transplant, liver pathology, coinfection with hepatitis B virus, and the immunosuppressive regimen. 9 Immunosuppression could promote viral replication in hepatocytes, enhancing the progression of liver disease. Posttransplant liver disease includes fibrosing cholestatic hepatitis, liver cirrhosis, hepatocellular carcinoma, and hepatic failure.…”
Section: Introductionmentioning
confidence: 99%